Boundaryless Career : A Bibliometric Analysis - Kumar, Sunil; Khan, Adil; Lochab, Anshu; Gupta, Vijay Prakash; Arora, Amit Kumar (Prabandhan: Indian Journal of Management, 2023)
Purpose : The research aimed to explore the research on boundaryless careers and found trends to set future research agendas. The study was a comprehensive bibliometric review of research on boundaryless careers. This study discovered significant and crucial aspects related to boundaryless career studies. Methodology : The research comprised 360 studies on boundaryless careers retrieved from the Web of Science (WOS) database. A bibliometric study of the database was performed to identify specific trends in boundaryless careers. This bibliometric analysis study employed the R program (biblioshiny package) for impact analysis and the Vosviewer program to determine the co-occurrence of authors, countries, and sources, among other things. The research revealed a knowledge deficit in the field of boundaryless careers. Findings : The study’s findings suggested that the concept of a boundaryless career was first published in 1995. Countries like the USA, UK, and China are leading in total production. The study also exhibited the results of co-citation and co-occurrence analysis in the paper. Practical Implications : The research added to the body of knowledge on boundaryless careers. The research findings would be valuable for future researchers and academicians pursuing careers in human resource management. Originality : The bibliometric study on a boundaryless career is unique. It highlighted the significance of boundaryless career orientation with other significant variables for future studies.